CATCH RATE FLUCTUATIONS OF SKIPJACK AND OTHER TUNA RESOURCES IN THE NORTHERN WATERS OF ACEH - Badrudin Badrudin; Sofri Bahar (Research Center for Fisheries, 1997)
The most dominant species of the ''large pelagic group